Sirt1 Promotes a Thermogenic Gene Program in Bone Marrow Adipocytes: From Mice to (Wo)Men - Artsi, Hanna; Gurt, Irina; El-Haj, Madi; Müller, Ralph; Kuhn, Gisela A.; Ben Shalom, Gal; Cohen-Kfir, Einav; Abramowitz, Eva; Kandel, Leonid; Safran, Ori; Dresner-Pollak, Rivka (Frontiers in Endocrinology, 2019)
ABSTRACT Bone marrow adipose tissue (MAT) is influenced by nutritional cues and participates in whole body energy metabolism. To investigate the role of Sirtuin1 (Sirt1), a key player in metabolism, in MAT, marrow adiposity was evaluated in inbred 5- month-old 129/Sv Sirt1 haplo-insufficient (Sirt1Δ/+) and wild type (WT) mice. Decreased expression of the thermogenic genes; PRDM16, PGC1α, Foxc2, Dio2, and β3AR was detected in whole tibiae but not in whole vertebrae (L4-L5) derived from Sirt1Δ/+ compared to WT female mice. Similarly, decreased expression of PRDM16 and PGC1α was observed in primary bone marrow mesenchymal stem cell (BM-MSC) cultures obtained from Sirt1Δ/+ compared to WT female mice, suggesting a cell autonomous effect of Sirt1 in BM-MSCs. No differences were detected in tibial or vertebral MAT in Sirt1Δ/+ compared to WT male mice. In vitro, Sirt1 over-expression in the mesenchymal embryonic fibroblast stem cell line C3HT101/2 increased PGC1α and PRDM16 protein level, and gene expression of β3AR, PRDM16, PGC1α, Dio2, FOXC2, UCP1 and the mitochondrial biogenesis markers TFAM and cytochrome C (Cyc1). Similarly, pharmacologic activation of Sirt1 by SRT3025 increased FOXC2, PGC1α, Dio2, TFAM and cytochrome C (Cyc1) expression in C3HT101/2 cells. Importantly, in human femoral BM-MSCs obtained from female patients undergoing hip operations for fractured head of femur or hip replacement for osteoarthritis, Sirt1 activation by SRT3025 increased PGC1α mRNA and protein level and reduced sclerostin. Blocking sclerostin by a monoclonal humanized antibody (Sc-AbII r13C7, Amgen) stimulated β3AR, PRDM16 and UCP1gene expression, and increased PGC1α protein level. These results show that Sirt1 regulates the bone marrow adipocyte phenotype in a gender- and site-specific manner in mice. Sirt1 activation and blocking sclerostin stimulate a thermogenic gene program in human BM-BMCs. These effects are mediated at least in part via PGC1α activation and sclerostin inhibition. The implications of these findings to bone health, hematopoiesis and whole body energy metabolism remain to be investigated.